Indigenous knowledge and research: The míkiwáhp as a symbol for reclaiming our knowledge and ways of knowing - Hart, Michael (First Peoples Child & Family Review, 2007)
This paper is based on the unique learning that the author obtained from various Cree and Anishinaabe Elders regarding Indigenous knowledge. The author’s experience with learning about Indigenous Knowledge is expressed through a review of the literature conducted on Indigenous knowledge and through symbolic imagery using the míkiwáhp (or “lodge”). Included is a discussion on appropriate considerations to utilizing Indigenous knowledge and its development in the context of colonial oppression over Indigenous peoples.